2022
DOI: 10.1101/2022.07.19.500631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of mRNA transcripts, protein isoforms, glycosylation and spatial localization of ACE2 and other SARS-CoV-2-associated molecules in human airway epithelium upon viral infection and type 2 inflammation

Abstract: SARS-CoV-2 infection continues to pose a significant life threat, especially in patients with comorbidities. It remains unknown, if asthma or allergen- and virus-induced airway inflammation are risk factors or can constitute some forms of protection against COVID-19. ACE2 and other SARS-CoV-2-related host proteins are limiting factors of an infection, expression of which is regulated in a more complex way than previously anticipated. Hence, we studied the expression of ACE2 mRNA and protein isoforms, together … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“… 53 Another recent study in preprint also demonstrated that IL‐13 decreased the expression of long ACE2 mRNA and reduced glycosylation of full‐length ACE2 protein, leading to reduction in the apical expression of ACE2 on the ciliated airway epithelial cells. 54 These data indicate that the inflammatory milieu may be an important factor affecting the expression of ACE2 and other SARS‐CoV‐2‐relevant receptors, and thus affect the susceptibility and infection. Genetic variation of allergic disease was associated with a lower risk of COVID‐19.…”
Section: Risk and Protective Factors For Susceptibility Severity And ...mentioning
confidence: 92%
See 1 more Smart Citation
“… 53 Another recent study in preprint also demonstrated that IL‐13 decreased the expression of long ACE2 mRNA and reduced glycosylation of full‐length ACE2 protein, leading to reduction in the apical expression of ACE2 on the ciliated airway epithelial cells. 54 These data indicate that the inflammatory milieu may be an important factor affecting the expression of ACE2 and other SARS‐CoV‐2‐relevant receptors, and thus affect the susceptibility and infection. Genetic variation of allergic disease was associated with a lower risk of COVID‐19.…”
Section: Risk and Protective Factors For Susceptibility Severity And ...mentioning
confidence: 92%
“…IL‐13 in combination with mucus was shown to reduce SARS‐CoV‐2 RNA by 90%–97% after inoculation of this virus in cultured human bronchial epithelial cells 53 . Another recent study in preprint also demonstrated that IL‐13 decreased the expression of long ACE2 mRNA and reduced glycosylation of full‐length ACE2 protein, leading to reduction in the apical expression of ACE2 on the ciliated airway epithelial cells 54 . These data indicate that the inflammatory milieu may be an important factor affecting the expression of ACE2 and other SARS‐CoV‐2‐relevant receptors, and thus affect the susceptibility and infection.…”
Section: Risk and Protective Factors For Susceptibility Severity And ...mentioning
confidence: 96%